CADMIUM AND LEAD TOXICITY IN TANNER grass Brachiaria arrecta - Pelaez P, Manuel; Casierra-Posada, Fanor; Torres R., Gerardo A. (Revista de Ciencias Agrícolas, 2014)
Physiopathologies in Brachiaria arrecta exposed to toxic contents of cadmium and lead were evaluatedin healthy 20-day old seedlings under hydroponic growth in the greenhouse of the Universidad Nacional of Colombia at Palmira. The study aimed to describe increasing symptoms due to poisoning, through the design of a rating scale of increasing damage. In addition, histological changes in roots, stems, and leaves were evaluated by high resolution light microscopy (HLRM). In this regard, the plant material was subjected to abiotic stress treatments with CdCl2 salts at 10 ppm concentration and Pb (NO3 )2 salts at 500 ppm. The main results showed greater deterioration in roots, stems, and leaves when plants were exposed to lead rather than cadmium. Extreme deformities were observed in cell walls of cortex cells and in the endodermis of the root. Leaf damage was notorious for both metals, especially in the chlorophyll parenchyma and in the deformity of epidermal walls of the adaxial and abaxial sides of the leaf. Deformities in the stems appeared in parenchymal filler cells with intense lead bioaccumulation. These results suggest that bioconcentration in plant tissues causes histological disorders, which may involve a food web, therefore, impacting on public health.